ON LINE AND DOUBLE MULTIPLICATIVE INTEGRALS - Bashirov, A. (Turkic World Mathematical Soc, 2013)
In the present paper the concepts of line and double integrals are modified to the multiplicative case. Two versions of the fundamental theorem of calculus for line and double integrals are proved in the multiplicative case.
Keywords: Multiplicative calculus; multiplicative line integral; independence on paths; Green's theorem